Was the Serpent’s Argumentation Conclusive? A Few Words That Go back to the Beginning of our Reasoning as a Gift to the Knower of Rationality - Lechniak, Marek (Analiza, racjonalność, filozofia religii: Księga jubileuszowa dedykowana Profesorowi Ryszardowi Kleszczowi. Nr 6 (2020), 2020)
The paper deals with the problem of transition in argumentation from a statement that everything except one is permitted to the conclusion that nothing is permitted; the motivation of the analysis is a story of the biblical serpent from Genesis 2-3. We suppose that the reasoning of the serpent is an example of nonconclusive argumentation, i.e.. an argument pars pro toto (apparent enthymeme) which can be often found in contemporary argumentations.